Herramienta software para optimizar la utilización de sistemas electromagnéticos de prospección geofísica en la Arqueología - Fco. Guzmán Navarro; M. Meco Gutiérrez; J.R. Heredia Larrubia; Fco. Pérez Hidalgo (Virtual Archaeology Review)
This article shows the applicability of ground penetrating radar (GPR) to archaeological investigations, with the aid of a software that allows increasing the resolution of the measurements. This software has been applied for the first time in Baelo Claud in order to obtain information about city´s decumanus and the crossing with cardines minores Furthermore, the developed tools has also been used to locate in Málaga and Puerto Real (Cádiz) common graves where the remains of about 2,600 victims of the Spanish Civil War rest and the repression that came before and after the civil conflict.